Baseline drinking water consumption and changes in body weight and waist circumference at 2-years of follow-up in a senior Mediterranean population. Issue 6 (June 2021) - Paz-Graniel, Indira; Becerra-Tomás, Nerea; Babio, Nancy; Serra-Majem, Lluís; Vioque, Jesús; Zomeño, María Dolors; Corella, Dolores; Pintó, Xavier; Bueno-Cavanillas, Aurora; Tur, Josep A.; Daimiel, Lidia; Zulet, M. Angeles; et al.
Summary: Background & aims: The association between drinking water consumption and adiposity has been poorly explored. Therefore, we aimed to analyse the associations between the frequency of drinking water consumption and body weight and waist circumference changes in an elderly Mediterranean cohort. Methods: A total of 1832 elderly participants (aged 55–75 years) with metabolic syndrome from the PREDIMED-Plus study with baseline data on drinking water and other beverages assessed by a validated 32-item Spanish fluid-intake questionnaire and with data on body weight (BW) and waist circumference (WC) at 1-year and 2-year were included in these prospective analyses. Multivariable linear regression models were fitted to assess the β-coefficients and 95% confidence interval (CI) for BW and WC changes in terms of categories of baseline drinking water consumption (tap water and bottled water). The theoretical effect on BW and WC of replacing several beverages with drinking water was assessed using mathematical models. Results: The baseline frequency of drinking water consumption was inversely associated with 1-year and 2-year changes in BW. β-coefficients (95%CI) across categories of water consumption (<2.5, 2.5 to <5, 5 to < 7.5, ≥7.5 servings/d) expressed in % of weight changes at 2 years of follow-up were 0.0,  −0.80 (−1.48,  −0.12),  −1.36 (−2.18,  −0.54), and −1.97 (−3.09,  −0.86), respectively. Individuals in the two highest categories of drinking water consumption (5 to < 7, and ≥7.5 servings/d) also showed a higher decrease in WC (expressed as % of change) after 2 years of follow-up: −1.11 (−1.96,  −0.25) and −1.45 (−2.66,  −0.24) compared to the reference intake (<2.5 servings/day), after adjustment for potential confounding factors. The theoretical replacement of soups, beers, spirits, hot beverages, dairy beverages, and other beverages group with drinking water was associated with greater reductions in BW at one- and two-years of follow-up. Conclusions: Drinking water consumption was inversely associated with 2-year adiposity changes in an elderly Mediterranean cohort at high cardiovascular risk. Our results also suggest that the consumption of drinking water instead of energy-containing beverages is associated with lower weight gain. The trial registration: ISRCTN89898870. Highlights: Drinking water consumption was inversely associated with 1-year and 2-year changes in BW. Increased drinking water was associated with higher reduction in waist circumference. The replacement of some energy containing beverages consumption by drinking water was associated with reductions on BW. Replacement of 1 mixed alcoholic beverage serving by 1 drinking water serving was associated with reductions on BW.